2018
DOI: 10.1001/jamadermatol.2017.4267
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hairdressers’ Knowledge and Self-efficacy to Detect Scalp and Neck Melanoma by Use of an Educational Video

Abstract: Black and O'Reilly had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis. Study concept and design: Roosta, Black, Woodley. Acquisition, analysis, or interpretation of data: All authors. Drafting of the manuscript: Roosta, O'Reilly, Black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 5 publications
(5 reference statements)
1
23
0
Order By: Relevance
“…In the developed countries, formal training programs are now being advocated to involve the hairdressers in scalp melanoma screening of the general public. [29][30][31][32][33][34]…”
Section: Clinical Evaluation and Diagnostic Work-up For Scalp Melanmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developed countries, formal training programs are now being advocated to involve the hairdressers in scalp melanoma screening of the general public. [29][30][31][32][33][34]…”
Section: Clinical Evaluation and Diagnostic Work-up For Scalp Melanmentioning
confidence: 99%
“…Understandably, hairdressers stand a far better chance of detecting any evolving scalp lesion at an early stage. In the developed countries, formal training programs are now being advocated to involve the hairdressers in scalp melanoma screening of the general public 29‐34 …”
Section: Clinical Evaluation and Diagnostic Work‐up For Scalp Melanomasmentioning
confidence: 99%
“…Seven studies were pre‐/post‐test design, 21–23,25–27 and 1 study was a cluster‐randomized controlled design 28 . All studies were conducted in the United States of America ( n = 8) 21–28 …”
Section: Resultsmentioning
confidence: 99%
“…Among these 8 studies, 2 studies sampled hair professionals alone, 23,24 2 studies sampled massage therapists alone, 22,27 3 studies sampled cosmetology students alone, 25,26,28 and 1 study sampled cosmetology students, esthetician students, and massage therapist students 21 . Sample sizes from the studies ranged from 31 to 254 21–28 . In most of the studies, >85% of participants were women 22–25,27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…showed that the overwhelming majority of 108 hairdressers interviewed are willing to learn more about skin cancer (91.7%) and to contribute for melanoma screening in the general population (93.5%). Educational video interventions effectively enhance knowledge and confidence of these professionals for melanoma detection 25 …”
Section: Discussionmentioning
confidence: 99%